Relações entre a qualidade fisiológica de sementes de pimentão e a variabilidade na produção de frutos - Brunes, Rélia Rodriguês (2013)
The objectives of this study were to evaluate the relationship between the physiological quality of chili pepper presenting different levels of vigor and variability in the yield of fruit in a protected environment, identifying the relationships between morphological variables and plant primary production. The experiments were conducted in a greenhouse at the Federal University of Santa Maria, in a randomized block design, with eight repetitions. The treatments consisted of four seed lots of hybrid Tiberius and Rubi Giant, with different vigor levels. Were measured at 50, 70 and 90 days after transplanting (DAT), plant height, height of the first fork, stem diameter, stem diameter below the first fork. In individual and combined harvests measured is the average weight of fruits, average production per plant, average production plant production, total production, average fruit length and average width of fruits analyzed in individual and combined harvests. Were diagnosed assumptions of univariate and multivariate mathematical model, estimates of the Pearson correlation coefficients and path analysis. The diameter and the diameter of the stem below the first bifurcation at 50, 70 and 90 days after transplanting (DAT) are less experimental variability in spring-summer and autumn-winter. Plants from seed vigor high and medium have similar behavior as the plant height at 50 and 70 days after transplanting, the height of the first fork, stem diameter, the diameter below the first fork, total production, the weight average fruit production and average plant. In the spring-summer season, plants from seed vigor high, medium and low, which have higher diameters of the first fork 50 and 90 days after transplanting tend to be more productive. In autumn-winter, there was no relationship of cause and effect on the total yield of pepper.